Nano metal oxide impregnated Chitosan-4-nitroacetophenone for industrial dye removal. Issue 13 (21st October 2021) - Mohamed, Hussein S.; Soliman, N.K.; Moustafa, A.F.; Abdel-Gawad, Omima F.; Taha, Rana R.; Ahmed, Sayed A.
ABSTRACT: Chitosan derivative nano-nitro-acetophenone was prepared by Schiff base reaction. The nano nitro-acetophenone was impregnated with CuO-CeO2 -Al2 O3 and CuO-CeO2 -Fe2 O3 nanocomposite to fabricate new organic-metal oxides nanocomposite of Chitosan-4-nitroacetophenone/CuO-CeO2 -Al2 O3 (NCCA) and Chitosan-4-nitroacetophenon/CuO-CeO2 -Fe2 O3 (NCCF). The new organic-metal oxides nanocomposite were prepared by wet impregnation technique, characterised by XRD, TEM, SEM, FTIR and TGA analysis, and used as an adsorbent for industrial disperse red 60 dye from wastewater. Dye adsorption isotherms, kinetics, thermodynamics, the effect of contact time and initial dye concentration, temperature, pH and adsorbent dosage were investigated. The reusability of NCCF and NCCA on dye removal was also studied. The results indicated that the dye removal% generally increased with decreasing dye initial concentration. The removal % decreased by increasing NCCF dosage while it increase by increasing the NCCA dosage from 0.05 to 0.1 g and after that it decreases again. The dye removal % increase with increasing temperature from 20°C to 80°C for NCCF adsorbent, while, it decreased at high temperature for NCCA adsorbent. Also, it decreased with increasing the initial pH of the solution from 2 to 8 for NCCF adsorbent. For NCCA adsorbent the percentage removal was increased with increasing the initial pH of the solution from 2 to 4 and after that it decrease again. The results showed also that NCCA was good reusable adsorbent, while, NCCF is not preferred for reuse for the same propose. The adsorption isotherm of dispersed red 60 dye onto NCCF and NCCA almost agreed with Langmuir isotherm and pseudo-second-order kinetics. The maximum amount of adsorbed dye is 92.8 and 88.5 mg/g onto NCCF at pH 2 and NCCA at pH 4, respectively. The thermodynamic results showed that the adsorption of disperse red 60 dye onto NCCF and NCCA is spontaneous, physical and endothermic adsorption process.